ИЗУЧЕНИЕ РАСПРОСТРАНЕННОСТИ НЕКОТОРЫХ ВИДОВ ГЕЛЬМИНТОЗОВ У ДЕТЕЙ В РЕСПУБЛИКЕ КАРАКАЛПАКСТАН - Тлеумбетова, Умитхан Жумамуратовна; Абдуллаева, Айсулыу Рауажовна (Children’s Medicine of the North-West, 2021)